PERANAN LEMBAGA PEMASYARAKATAN (LAPAS) DALAM PEMBINAAN NARAPIDANA PEREMPUAN DI LAPAS PEREMPUAN KELAS IIA PALEMBANG - Abdullah, Alexander; Hidayah, Ardiana (Solusi, 2024)
Palembang Class IIA Women's Prison is one of the implementing units of the prison punishment system that is tasked with fostering female prisoners. The problem in this study is how the role of the Prison in fostering female prisoners in the Palembang Class IIA Women's Prison. In addition, it also raises the issue of what are the obstacles in fostering female prisoners in the Palembang Class IIA Women's Prison. This study is an empirical legal research located in the Palembang Class IIA Women's Prison. The role of the Correctional Institution in fostering female prisoners in the Palembang Class IIA Women's Prison is the guidance carried out in two areas, namely personality development and independence development. Personality development consists of personality development in the fields of religion, sports and arts, national and state awareness, the environmental field and development of integrating oneself with the Community. Prisoners are given independence development as regulated in the Correctional Law so that they become activities that produce goods and services that have benefits and added value. The obstacles faced in fostering female prisoners in the Palembang Class IIA Women's Prison are limited officers and excess capacity of inmates. It is recommended that personality development for inmates be carried out continuously and increase independence development by taking a more tailored approach to the interests and talents of inmates. It is hoped that there will be efforts from the government to overcome excess capacity in correctional institutions.